Compositional insights on the association between physical activity and sedentary behavior on momentary mood in daily life. (January 2022) - Giurgiu, Marco; Ebner-Priemer, Ulrich W.; Dumuid, Dorothea
Abstract: Objective: Given the increasing number of mental disorders, a growing body of studies now focuses on the relationship between physical activity (PA), sedentary behavior (SB), and mental health. However, momentary mechanisms and interrelatedness between PA, SB, and mood in daily life are highly understudied. Methods: To investigate whether the composition of light physical activity (LPA), moderate-to-vigorous physical activity (MVPA), and SB influences mood, we conducted an Ambulatory Assessment study in the everyday life of 103 university students over five days. We measured PA and SB via accelerometers and assessed mood up to six times each day on smartphone diaries. We combined compositional data analyses (CoDA) with multilevel modeling to analyze within-person effects of the behavioral composition on mood. Results: Higher ratio of the SB to LPA and MVPA composition within the 60 min prior to a diary rating negatively influenced valence (p = 0.006) and energetic arousal (p < 0.001). Furthermore, a higher ratio of LPA to SB and MVPA positively influenced energetic arousal (p < 0.001) and a higher ratio of MVPA to SB and LPA positively influenced valence (p = 0.004) and energetic arousal (p = 0.022). Simulation analyses revealed that replacing 20 min of SB with PA can influence mood rating up to 3.39 units [range from 0 –100]. Conclusions: Findings suggest that minutely replacements of SB with PA may lead to mood enhancements. Given the high prevalence of mental disorders, more studies are warranted to deepen the understanding of momentary compositional mechanisms between SB, PA, and mood. Applying CoDA to intensive longitudinal data can serve as a starting point to identify the optimal composition of SB, LPA, and MVPA for mood enhancements in everyday life. Highlights: Ratio of SB to LPA and MVPA composition negatively influenced two mood dimensions. Ratio of LPA to SB and MVPA composition positively influenced energetic arousal. Ratio of MVPA to SB and LPA composition negatively influenced two mood dimensions. Minutely replacements of SB with PA may lead to mood enhancements.